IMPLEMENTASI MEDIA PEMBELAJARAN DALAM MODEL TEAM BASED LEARNING PADA PEMBELAJARAN AKIDAH AKHLAK DI MTS AL - HIDAYAH LAMPUNG - Riska Melinda; Chairul Anwar; Listiyani Siti Romlah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning Akidah Akhlak in madrasahs still faces challenges in the form of low student participation and activeness due to the dominance of conventional teaching methods. This condition highlights the need for learning innovations that can create interactive, collaborative, and engaging learning environments. One alternative approach is the use of digital learning media such as Wordwall combined with the Team Based Learning (TBL) model. This study employed a qualitative approach with a descriptive research design conducted at MTs Al-Hidayah Lampung. The research subjects consisted of Akidah Akhlak teachers and students in the observed class. Data were collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing. The findings indicate that lesson planning was conducted by preparing lesson plans that integrated Wordwall media with the stages of the TBL model. The learning implementation proceeded systematically through teamwork, group discussions, and Wordwall-based evaluation activities, which enhanced students’ activeness, collaboration, and learning enthusiasm. Learning evaluation covered cognitive, affective, and psychomotor aspects, showing an improvement in students’ learning outcomes. Therefore, the implementation of Wordwall media within the Team Based Learning model contributes positively to the process and outcomes of Akidah Akhlak learning